Modern weapons and military equipment for the issue 1-2021 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Analysis: Top most modern 6x6 wheeled self-propelled howitzer; Serbia test-fires indigenous RLN-IC/170 short-range SAM